Impact of subsidized fortified wheat on anaemia in pregnant Indian women - Chakrabarti, Suman; Kishore, Avinash; Raghunathan, Kalyani; Scott, Samuel P. (John Wiley & Sons, 2019)
The World Health Assembly called for a 50% global anaemia reduction in women of reproductive age (15–49 years of age) from 2012 to 2025. India accounts for the most cases of anaemia in the world, and half of all pregnant Indian women are anaemic. In India, the government implemented a 4‐year food‐based safety net programme from 2008 to 2012 involving the provision of fortified wheat flour through its public distribution system. We assessed programme impact on anaemia among pregnant women (n = 10,186) using data from the 2002–2004 and 2012–2013 Indian District Level Health Surveys. The difference‐in‐differences method was used to estimate the impact on haemoglobin (Hb) and anaemia in pregnant women living in northern India (Punjab) and southern India (Tamil Nadu), with pregnant women in neighbouring states without wheat fortification programmes serving as controls. In northern India, we found no impact on Hb (β = −0.184, P = 0.793) or anaemia reduction (β = −0.01, P = 0.859), as expected, given that the intervention targeted only nonpoor households and demand for fortified wheat was low. In southern India, where intervention coverage was high, we found no impact on Hb (β = −0.001, P = 0.998) but did see an impact on anaemia reduction (β = −0.08, P = 0.042), which was unexpected given low consumption of wheat in this predominantly rice‐eating region. India's wheat fortification programmes were largely ineffective in terms of reducing anaemia among pregnant women. As policymakers expand fortification programs, it is critical to ensure that the fortified food is universally available and distributed widely through well‐functioning and popular outlets.